The Influence of national culture dimensions on agile implementations in the South African software development context - Matthews, Kirwin (Department of Information Systems, 2023)
Culture plays a role in how Agile frameworks are utilised and implemented. Agility requires the active involvement of team members and is said to be suitable in contexts where there is a horizontal hierarchy (low power distance) and where flexibility and spontaneity (low uncertainty avoidance) are emphasised. Cultures from Anglosphere countries, where Agile methodologies originate from, and Nordic countries, are closest aligned to Agile values. Since Agile values are based on Western culture, there is a need to investigate their suitability for cultures that have different values such as South Africa. South Africa offers an interesting context of study due to its heterogeneous cultural grouping. While studies have been conducted to investigate the influence of national culture on Agile implementations in Western and Eastern country contexts, there is no research that explores the influence of national culture and the implementation of Agile methodologies in the South African software development context. Furthermore, few studies have focused on the effect of cultural differences within software engineering in general. The purpose of this study was to describe how national culture influences Agile implementations (roles, processes, and artifacts) within the South African software development context. The study was deductive as national culture frameworks were employed. This study was interpretive and was executed using a qualitative, interview research strategy directed at Agile practitioners in South African software development teams. Data was collected from twenty-six participants from across two major cities in South Africa through online semi-structured interviews. The thematic analysis technique was used to analyse the data. Findings reveal that national culture dimensions influence the Agile roles, processes, and artifacts. The basis for contributions was based on the empirical research of this study, specifically in relation to 1) insights into the role of a consolidated set of cultural dimensions on Agile practices 2) implications for agility by discussing findings considering Agile principles and values 3) findings mapped to the Complex Adaptive Systems (CAS) theory principles. A key finding was that South Africa does not demonstrate a homogenous cultural trait. Instead, various cultural traits are revealed, which brings more complexity to the Agile implementations. Thirty-two propositions relating to how the various dimensions influence Agile roles, processes, and artifacts were developed by the researcher. The key findings reveal that various national culture dimensions influence the decision-making process, the degree of Sprint interruptions, participation in Agile ceremonies, adherence to policies and prescribed Agile practices, how teams reach agreement, and approaches to process improvement and Sprint Planning. Lastly, in this study, the practical contributions are insights into the current context where national culture dimensions influence large-scale Agile frameworks such as SAFe, and small-scale Agile frameworks such as Scrum in South African software development teams. In this regard, it can help inform Agile implementations in practice, and therefore help managers and teams curate Agile teams for appropriate environments.